2020
DOI: 10.33889/ijmems.2020.5.6.088
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A Bibliometric Analysis and Insights

Abstract: The current outbreak of the coronavirus disease has left the whole world traumatised. The illness triggered by the novel coronavirus is named as COVID-19. It is pre-fixed with the word “novel” because it comes under the new strain of the virus that has not been reported before. This virus outbreak has disrupted human life in the most petrifying way worldwide. The present study aims to analyse the work done in this field through a state-of-the-art review of articles based on COVID-19 and discuss the current tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Some of them discussed the global scientific research on COVID-19, and most of these publications analyzed the scientific productions related to COVID-19 (Costa et al, 2020;Dehghanbanadaki et al, 2020;Farooq et al, 2021;Mohadab et al, 2020;Oliveira et al, 2021). Meanwhile, in these publications, some authors summarized the hotspots and explored the future trends of the research (Gautam et al, 2020;Lou et al, 2020;Mao et al, 2020;Yang et al, 2020;Yu et al, 2020). Also, there have been some studies that analyzed the international cooperation and interdisciplinary cooperation situations (Dehghanbanadaki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them discussed the global scientific research on COVID-19, and most of these publications analyzed the scientific productions related to COVID-19 (Costa et al, 2020;Dehghanbanadaki et al, 2020;Farooq et al, 2021;Mohadab et al, 2020;Oliveira et al, 2021). Meanwhile, in these publications, some authors summarized the hotspots and explored the future trends of the research (Gautam et al, 2020;Lou et al, 2020;Mao et al, 2020;Yang et al, 2020;Yu et al, 2020). Also, there have been some studies that analyzed the international cooperation and interdisciplinary cooperation situations (Dehghanbanadaki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…USA ranked second row. Japan and European countries such as United Kingdom, Germany and Italy followed these countries 1,3,8 . In a study, authors stated that journal publications on COVİD-19 suggested scientists to collaborate and launch the joint research projects.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, a contagious disease which is caused by novel coronavirus (SARS-CoV-2), is still spreading globally 1,2 . SARS-CoV-2 is a spherical, enveloped, positive-sense, single stranded, RNA coronavirus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis derived from the bibliometric method is able to compare the countries that contributed to the publications according to their respective fields. Bibliometric study has been applied in a wide range of fields including the COVID-19 pandemic (Gautam et al 2020 ), environmental (Zhang et al 2020 ), agricultural (Luo et al 2020 ), sustainable development (Ye et al 2020 ), Chinese loess plateau (Zhang and Chen 2020 ), accounting (Merigó and Yang 2017 ), economic (Bonilla et al 2015 ), linguistic decision making (Yu et al 2016 ) and fuzzy research (Merigó et al 2015 ). Bibliometric studies contribute to several advantages such as: (a) reveal the importance of research in the related field, (b) reveal the development of research based on the institution and performance, (c) enable researchers to use the publication of related studies for future studies, and (d) to improve the knowledge of new researchers.…”
Section: Introductionmentioning
confidence: 99%